Deconstructing the Iilusion of Shopeefood Advertisements Through Simulacra Theory of Indonesian Main Course - Triana, May Devi; Naibaho, Sriwi Anceli; Sihite, Sepania Handayani; Lawolo, Claudia Lisya (Jurnal Akuntansi Hukum dan Edukasi, 2025)
This study explores the application of Jean Baudrillard's theory of simulacra and hyperreality in the analysis of ShopeeFood digital advertisements. The research aims to examine how food imagery, promotional language, and consumer experiences in these ads construct a hyperreal representation that blurs the line between reality and simulation. Using a qualitative content analysis method, the study investigates selected ShopeeFood video advertisements from social media platforms such as YouTube and Instagram. The findings reveal that ShopeeFood ads do not merely promote food delivery services but construct a simulated consumer desire through idealized visuals, exaggerated discounts, and emotional storytelling. These elements detach the advertised content from the real experience of ordering and consuming food, instead creating a hyperreality where the image becomes more "real" than reality itself. This research highlights the significance of digital advertising ethics and the need for critical consumer awareness in the postmodern media landscape, where simulations often dominate perceptions of consumption.